Population structure, size and sex ratio in Podocnemis unifilis (Testudines, Podocnemididae) in the Guaporé river (RO), northern Brazil - Fachín-Terán, Augusto; Vogt, Richard C. (Phyllomedusa: Journal of Herpetology, 2004)
Population structure and sex ratio of Podocnemis unifilis was studied from June to November 1989 and from March to June 1990 in the Guaporé river and its tributaries São Domingos and São Miguel, in the municipality of Costa Marques, Rondônia, Brazil. The margins of these rivers are not altered much by human activities and the water is not polluted in any way. Turtles were captured using 12 fyke nets. Around 1 % of the captured turtles died using this method. The majority of the turtles was captured in the bays and oxbows (55.8%) and when the water level of the river was declining (N=785). The proportion of adults (73.4 %) in the sample was about three times higher than that of juveniles (26.6 %). The distribution of carapace length in males formed a normal curve, while that of females showed no well-defined pattern. The sex ratio of adults in this population was 9.8 males per female.